Pakar nutrisi pemilihan set makanan RM3.50 UPM satu usaha yang bagus - Mohd Azhari, Nurul Ezzaty (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2022)
SERDANG, July 20 – Universiti Putra Malaysia (UPM) came up with an initiative to set the price of quality set meals as low as RM3.50 for its students starting July 8.